Implementation Of Islamic Religious Education Through Religious Culture In Schools - Indra Iskandar; Fitriyani Kosasih (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study investigates the implementation of Islamic Religious Education through religious culture in two public schools with distinct characteristics: SMAN 9 Garut (general senior high school) and SMKN 7 Garut (vocational high school). Employing a qualitative, descriptive case study approach, the research explores how religious culture is developed, its supporting and inhibiting factors, and its impact on students' religious character. Findings reveal that both schools utilize routine, incidental, and daily cultural programs, demonstrating similarities in execution while adapting to their specific contexts. Success factors include strong leadership commitment and active IRE teacher involvement, whereas challenges stem from varying student motivation and limited non-IRE teacher engagement. Notably, SMKN 7 Garut faces additional constraints due to facility limitations and demanding vocational schedules. The study concludes that religious culture significantly shapes students' character across spiritual, social, academic, and vocational dimensions, offering an adaptive model for IRE integration and practical recommendations for educational administrators